High-frequency lake data benefit society through broader engagement with stakeholders: a synthesis of GLEON data use survey and membe rexperiences. Issue 4 (1st January 2016) - Smyth, Robyn L.; Caruso, Alicia; Borre, Lisa; Zhu, Guangwei; Zhu, Mengyuan; Hetherington, Amy L.; Jennings, Eleanor; Klug, Jennifer L.; Piccolo, Maria Cintia; Rusak, James A.; Weathers, Kathleen C.; Wigdahl-Perry, Courtney
Abstract: The Global Lake Ecological Observatory Network (GLEON) has a tremendous opportunity to facilitate greater public understanding of lakes and enable evidence-based decision making for freshwater ecosystems with high frequency data. To investigate this potential as well as the scope of outreach activities currently underway, we surveyed the 46 GLEON sites active as of 2013 about the uses of the high-frequency lake data (HFD). Of the 26 who responded, 69% engaged in or were aware of the use of GLEON HFD beyond academics. To highlight some of the outreach activities conducted in collaboration with GLEON scientists, we elaborate on 3 categories of data use: (1) engaging with citizens, (2) educating students and teachers, and (3) aiding in decision making. When synthesized with a discussion of examples of broader engagement activities across the network from the perspective of participants, the results suggest GLEON's network science approach enables the diffusion of ideas and tools for conducting effective outreach. Results also point to opportunities for GLEON to build on existing experience to encourage greater engagement of member scientists in lake conservation, restoration, and management. In light of the growing challenges in managing water quality and quantity, our findings will help determine best practices and provide guidance to scientists on how to engage a broader range of stakeholders in lake research and management.